Determinasi Gaya Hidup Potensial Terhadap Kejadian Penyakit Jantung: Studi Komparatif pada Pegawai dan Petani di Kabupaten Gowa - Aqiilah Tun Humairah; Emmi Bujawati; Sukfitrianty Syahrir; Rimawati Aulia Insani Sadarang; Mubarak Mubarak (Jurnal Kesehatan Indonesia, 2025)
Cardiovascular disease is one of the leading causes of death worldwide, with lifestyle risk factors contributing significantly to its occurrence. This study aimed to determine the association between potential lifestyle risk factors and the incidence of heart disease among employees and farmers in Gowa District in 2025. A quantitative approach with an observational analytic design was applied. The study involved 160 respondents selected through purposive sampling. Data were analyzed using univariate and bivariate methods with the chi-square test. The results showed that, among employees, there were significant associations between physical activity (p=0.004), smoking behavior (p=0.021), and sleep quality (p=0.040) with heart disease. Meanwhile, among farmers, physical activity (p=0.050) and smoking behavior (p=0.042) were significantly associated, whereas knowledge level, sleep quality, and dietary patterns were not. In conclusion, physical activity and smoking behavior were identified as dominant risk factors associated with the incidence of heart disease in both employees and farmers.